Vasculitides and glomerulonephritis associated with Staphylocococcus aureus infective endocarditis: cases reports and mini-review of the literature. (17th August 2020) - Brunet, Aurélie; Julien, Gautier; Cros, Amandine; Beaudoux, Olivia; Hittinger-Roux, Ambre; Bani-Sadr, Firouze; Servettaz, Amélie; N'Guyen, Yohan
Abstract: We reported two cases of Staphylococcus aureus Infective Endocarditis associated with vasculitides and glomerulonephritis respectively, before conducting an online search of previously published similar cases reports. Twenty five references were selected: 15 cases of glomerulonephritis; 2 cases of vasculitis and 8 cases involving both glomerulonephritis and vasculitis. Vasculitides and glomerulonephritis associated with Staphylococcus aureus definite Infective Endocarditis have been reported since 1976. All cases except one described clinical symptoms occurring before or during initial antibiotics treatment. Except kidney, organs that were more frequently affected by vasculitis process were skin, gastrointestinal tract and peripheral nerve and the vessels involved were small to medium size vessels. When antineutrophil cytoplasmic antibodies were evidenced (6 out of the 25 cases (24%)), kidney was the most frequently affected organ. The most commonly observed pattern in Kidney biopsy was membranoproliferative glomerulonephritis with endocapillary proliferation sometimes associated with extra capillary crescents, whether or not antineutrophil cytoplasmic antibodies were evidenced. Right-sided Infective Endocarditis (especially in intravenous drug users) were overrepresented (14 of the 25 cases (56.0%)) in this review. Besides antibiotics, corticosteroids were the most frequently prescribed immunosuppressive treatment both for vasculitides or glomerulonephritis. KEY MESSAGES: Vasculitides and glomerulonephritis associated with Staphylococcus aureus definite Infective Endocarditis have been reported since 1976. Except kidney, organs that were more frequently affected (by small to medium size vessel vasculitis) were skin, gastrointestinal tract and peripheral nerve. The most commonly observed pattern in Kidney biopsy was membranoproliferative glomerulonephritis with endocapillary proliferation and right-sided Infective Endocarditis (especially in intravenous drug users) were overrepresented in this review.